Development of silent reading fluency and reading comprehension across grades 1 to 9: unidirectional or bidirectional effects between the two skills? - Psyridou Maria; Tolvanen Asko; Niemi Pekka; Lerkkanen Marja-Kristiina; Poikkeus Anna-Maija; Torppa Minna (SPRINGER, 2025)
Purpose: This study examines the developmental interplay between silent reading fluency and reading comprehension from Grade 1 to Grade 9 (age 7 to 15) in a large Finnish sample (N = 2,518). Of particular interest was whether the associations are bidirectional or unidirectional.
Methods: Children's silent reading fluency and reading comprehension skills were assessed using group-administered tests, at seven time points, in Grades 1, 2, 3, 4, 6, 7, and 9. A random intercept cross-lagged panel model with latent factors was used to identify between- and within-person associations between silent reading fluency and reading comprehension. The use of latent factors allowed for the controlling of measurement error.
Results: The model showed that silent reading fluency and reading comprehension correlated at the between-person level, indicating that those who were proficient in one reading skill were typically good at the other also. At the within-person level, however, only some developmental associations emerged: in the early reading acquisition phase (Grade 1-2), silent reading fluency predicted reading comprehension, and in adolescence, reading comprehension weakly predicted silent reading fluency (Grade 7-9).
Conclusions: The results thus suggest only weak developmental within-person associations between silent reading fluency and comprehension, although some unidirectional associations emerged with a change in the direction of the associations over time.